Prognostic role of plasma galectin-3 levels in acute coronary syndrome. Issue 8 (December 2020) - Obeid, Slayman; Yousif, Nooraldaem; Davies, Allan; Loretz, Ruben; Saleh, Lanja; Niederseer, David; Noor, Husam A; Amin, Haitham; Mach, François; Gencer, Baris; Räber, Lorenz; Windecker, Stephan; et al.
Aim: Cystatin C, neutrophil gelatinase-associated lipocalin and galectin-3 have emerged as biomarker candidates to predict cardiovascular outcomes and mortality in the general population as well as in patients with coronary artery or renal disease. However, their predictive role and clinical utility in patients with acute coronary syndromes alone or in combination beyond currently used risk scores remains to be determined. Methods and results: Cystatin C, neutrophil gelatinase-associated lipocalin, and galectin-3 were measured in plasmas of 1832 patients at the time of presentation with acute coronary syndromes requiring percutaneous coronary intervention or coronary artery bypass grafting. The primary outcomes were major adverse cardiac and cerebrovascular events (defined as the composite of all-cause mortality, cerebrovascular events, any repeat revascularization or myocardial infarction) and all-cause mortality after 1 year and occurred in 192 (10.5%) and 78 (4.3%) of patients, respectively. All three biomarkers were increased in those with major adverse cardiac and cerebrovascular events compared with those without ( p <0.001). However, only galectin-3 (all-cause mortality: hazard ratio=1.027 (95% confidence interval (1.011–1.043); p =0.001), major adverse cardiac and cerebrovascular events: hazard ratio=1.025 (95% confidence interval (1.012–1.037); p <0.001)) but not cystatin C nor neutrophil gelatinase-associated lipocalin emerged as independent predictors of both major adverse cardiac and cerebrovascular events and death. The risks were particularly high in the highest quartile of galectin-3. The integration of galectin-3 into the global registry of acute coronary events (GRACE) score improved the prediction of major adverse cardiac and cerebrovascular events and all-cause mortality significantly. The areas under the receiver operator characteristics curves increased from 0.6701 to 0.6932 for major adverse cardiac and cerebrovascular events ( p =0.0474) and from 0.804 to 0.8199 for all-cause mortality ( p =0.0197). Finally, we applied net reclassification improvement index using different cut-offs for major adverse cardiac and cerebrovascular events which showed negative results (for the cut-offs of 5% and 15%, net reclassification improvement index 0.028, p =0.586, for the cut-offs of 10% and 20%, net reclassification improvement index 0.072, p =0.1132 and for the cut-offs of 10% and 30% the net reclassification improvement index is 0.0843, p =0.077). Conclusion: In acute coronary syndromes patients, galectin-3 has moderate prognostic accuracy, provides statistically significant incremental value in some, but not all models, and that the magnitude of any improvement would seem of questionable clinical value.